PENGARUH FITOHORMON PADA KULTUR KALUS TANAMAN GAJAH BERANAK (Gonothalamus sp.) SEBAGAI RANCANGAN POSTER DIGITAL MATERI BIOTEKNOLOGI MODERN (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study was conducted to determine the effect of phytohormones concentration on callus culture of gajah beranak (Goniothalamus sp.) as a digital poster design for high school modern biotechnology materials carried out in December 2021 - February 2022. This study consisted of two stages, namely: stage I culture callus gajah beranak (Goniothalamus sp) using an experimental method carried out in the UIR biotechnology laboratory with a completely randomized design (CRD) factorial 6x2 with 3 replications. Phase II is the design of a digital poster which is carried out on the campus of the UR biology education study program. Parameters observed were callus emergence time (HSK), percentage of callus number (%), callus width (cm) and callus texture. Data analysis used ANOVA and DMRT follow-up test at 5% level. The results showed that the concentration of phytohormones had a significant effect on callus culture of gajah beranak (Goniothalamus sp.). The best concentration of phytohormones was in the treatment with a concentration of 5 mgL-1 hormone 2,4-D and 0,5 mgL-1 hormone BAP resulted in the fastest callus emergence time of 22.33 HSK with 100% callus percentage, callus width 1.03 cm and embryogenic crumb texture callus for cell suspension culture. The research data was designed as a digital poster media on modern biotechnology material for class XII SMA KD 3.10 and 4.10.Key Words: Phytohormones, Callus Culture, Digital Poster.